Face-to-Face Storytelling - Brandon Telg; Jaron Jones; Ricky Telg (EDIS)
In the agricultural industry, telling your story is critical for establishing your operation’s identity. Communicating face-to-face is one method of getting your message to the public. This 2-page fact sheet presents tips and strategies for delivering your story to a live audience. Written by Brandon Telg, Jaron Jones, and Ricky Telg, and published by the UF Department of Agricultural Education and Communication, July 2015.